Requirements specification of a software-intensive system in the health domain: An experience report - Arenas, Carolina; Garcés, Lina; Carmona, María J. C.; Simões, Claudia Marquez (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2020)
A great variety of methods, techniques, or approaches have been proposed to systematize and facilitate activities of software systems’ requirements elicitation and specification. Each of them has its specific purposes and contributes in its own way for obtaining a good understanding of software requirements. However, in practice, using an unique method is not enough to cover all tasks required during software-intensive system's requirement engineering. This work does not aim to propose a new or a hybrid method, since each software project has its own characteristics, and methods must be selected and sometimes adapted to fit in each project specificities. This work reports the authors’ experience on how different methods were used together in a coordinated way for requirements specification. Also, possible benefits and drawbacks found by combining methods are also presented.